THE EFFECT OF SERVICE QUALITY AND BRAND IMAGE ON CONSUMER SATISFACTION AT PT. SUZUKI FINANCE INDONESIA KESIMAN DENPASAR - Wulan Anggreni, Ni Komang Sri; Ni Wayan Widi Astuti; Putu Siti Firmani (Arthaniti Studies, 2024)
Based on observations made at PT. Suzuki Finance Indonesia Kesiman Denpasar, it can be seen the number of consumers who buy car products at PT. Suzuki Finance Indonesia Kesiman Denpasar from 2021 - 2023. The lowest number of consumers in 2021 was 1,273, while the highest number of consumers iin 2022 was 1,411, resulting in a decrease in the number of consumers in i2023 to 1,345. This research aims to determine the influence of service quality and ibrand image on consumer satisfaction at PT. Suzuki Finance Indonesia Kesiman Denpasar. This research uses a causal associative quantitative approach through observation, interviews, documentation and questionnaires in data collection. The number of respondents in this research was 93 consumers.The results of this study show that (1) There is a partial influence of Service Quality on Consumer Satisfaction as evidenced by the results of the tcount test of 6,599 > ttable 1,986 with a significant value of 0.000 < 0.05; (2) There is a partial influence of Brand Image on Consumer Satisfaction as evidenced by the results of the tcount test of 11,476 > ttable 1,986 with a significant value of 0.000 < 0.05; (3) There is a simultaneous influence on Service Quality and Brand Image towards Consumer Satisfaction as seen from the results of the Fcal > Ftabel test of 78.987 > 3.10 with a significant value of 0.000 < 0.05. The results of the determination coefficient test showedthat the magnitude of the Adjusted R square value was 0.617 which means that 63.7% of the variation in Consumer Satisfaction was influenced by Service Quality and Brand Image, while the remaining 36.3% was influenced by other factors that were not included in this study variable.